2019
DOI: 10.1186/s12974-019-1446-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NF-κB p50 function synergistically augments microglial priming in the middle-aged brain

Abstract: BackgroundWhile NF-κB p50 function is impaired in central nervous system disease, aging in non-CNS tissues, and response to reactive oxygen species, the role of NF-κB p50 in aging-associated microglial pro-inflammatory priming is poorly understood.MethodsMale NF-κB p50+/+ and NF-κB p50−/− mice at three different ages (1.5–3.0 month old, 8.0–11.0 month old, and 16.0–18.0 month old) were treated with LPS (5 mg/kg, IP) to trigger peripheral inflammation, where circulating cytokines, neuroinflammation, microglia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…Taken together, the predominant extranuclear localization of NF-κB p65 and the absence of correlation between MY10 potentiation of LPS-induced microglial priming in the PFC and prototypical pro-inflammatory signaling, the data suggest the existence of an unknown promoter of microgliosis. This circumstance of potentiation of microgliosis together with the decrease of NF-κB p65 has been described in other contexts such as aging 26 and point to a novel RPTPβ/ζ mediated signaling mechanism of potentiation of LPS-induced microglial activation, which is independent of the NF-κB p65 pathway. However, a limitation of this study has to be noted.…”
Section: Discussionsupporting
confidence: 66%
“…Taken together, the predominant extranuclear localization of NF-κB p65 and the absence of correlation between MY10 potentiation of LPS-induced microglial priming in the PFC and prototypical pro-inflammatory signaling, the data suggest the existence of an unknown promoter of microgliosis. This circumstance of potentiation of microgliosis together with the decrease of NF-κB p65 has been described in other contexts such as aging 26 and point to a novel RPTPβ/ζ mediated signaling mechanism of potentiation of LPS-induced microglial activation, which is independent of the NF-κB p65 pathway. However, a limitation of this study has to be noted.…”
Section: Discussionsupporting
confidence: 66%
“…Nuclear factor κB1, however, may also have beneficial effects because NF-κB1-deficient EAE mice showed more infiltrated inflammatory cells in the CNS than control mice. Consistently, p50-deficient mice exhibit augmented microglial proinflammatory responses after peripheral injection with lipopolysaccharide (94).…”
Section: T Cellsmentioning
confidence: 62%
“…Support for this concept comes from animal experiments in which p50-deficient mice developed a more severe neutrophilic inflammation with a highly elevated TNF-α expression [ 29 ]. Furthermore, a recent study also reported an amplified degree of neuroinflammation in p50 knock-out mice together with an excessively increased TNF-α expression [ 30 ]. Therefore, a lack of nuclear p50 activity, as was present in D-allele carriers in our study, appears to be the main cause of the genotype-dependent aggravated inflammatory response in septic patients.…”
Section: Discussionmentioning
confidence: 99%